Free Radicals Generated by Post-Prandial Oxidative Burst in the Early Alterations of Vascular Contractility - Peluso, Ilaria; Manafikhi, Husseen; Palmery, Maura (Clinical Immunology, Endocrine & Metabolic Drugs (Discontinued), 2014)
Repeated high fat and high carbohydrate meals (HFHCM) generate atherosclerosis, isolated systolic hypertension (ISH), autonomic and endothelial dysfunction. Consequently, old people are particularly susceptible to both flowmediated dilation (FMD) impairment and postprandial hypotension. Despite the mounting evidence that free radicals substantially alter blood pressure and endothelial function, the mechanisms that outline these phenomena are unclear. We have reviewed the effects of the free radicals generated by post-prandial oxidative burst on vascular contractility. Postprandial endotoxemia seems to play a crucial role in both oxidative burst and inflammatory response after meal. Oxidative burst produces both reactive oxygen species (ROS) and reactive nitrogen species (RNS). The reviewed results do not support the hypothesis that a sparing NO• effect is the primary cause of the early alteration of vascular contractility induced by oxidative burst. The contrasting results of various ROS seem to be due to the differentiated effect or toxicity to endothelium or vascular smooth muscle, while lypopolisaccaride, peroxinitrite and peroxyl radicals induce hypotension. On the other hand, immune activation improves sympathetic nervous system (SNS) activity and the compensatory adrenergic response to postprandial hypotension has anti-inflammatory activity. Besides, insulin inhibits post-prandial oxidative burst, post-prandial oxidative stress and inflammation activate the xanthine oxidase and induce the antioxidant enzymes. In conclusion, repeated HFHCM meal ingestion could induce hyper-insulinaemia, chronic SNS and antioxidant enzymes activation. These defensive mechanisms, to both post-prandial hypotension and inflammation, generate autonomic dysfunction and FMD impairment, whereas the chronic oxidative stress induces structural changes in the arteries leading to ISH.
Keywords: reactive nitrogen species